(untitled) (Baghdad Science Journal, 2015)
The wall of the esophagus in Mabuya aurata septemaeniata as in high vertebrates consists of four layers, mucosa, submucosa,muscularis and serosa. Mucosa forms many unorganized short and long folds penetrate inside the esophageal cavity. Mucosa contains two sub layers, first one is lining epithelium which includes two types of cells, simple ciliated columnar epithelial cells and goblet cells, second one is lamina properia. Mucosa does not have muscularis mucosa. There is no esophageal glands within esophagus. Many special stains were used as (Periodic Acid Schiff (PAS)) to detect Carbohydrates in goblet cells. Alcian blue were used to detect the amount of goblet cells within lining epithelium. Alcian blue + PAS together confirm that the secreted mucin from goblet cells was acidic.